ChemInform Abstract: An Efficient Two‐Step Synthesis of Novel 2‐Amino‐Substituted Pyrazolo[1, 5‐a][1, 3, 5]triazines. Issue 27 (13th June 2013) - Insuasty, Henry; Insuasty, Braulio; Castro, Edison; Quiroga, Jairo; Abonia, Rodrigo
Abstract Substrates (I), prepared according to a recently reported procedure, undergo amination/cyclization upon treatment with amines in the presence of HgCl2/NEt3.